FACTORS AFFECTING IRON AND FOLICACID CONSUMPTION AMONG ADOLESCENTS: A LITERATURE REVIEW - Putri, Stevani Basuki; Ulfiana, Elisa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Adolescents who experience anemia in 2018 reach 48.9%. The Indonesian government's program on taking blood tablets is done once a week. Anemia in adolescents in 2013 to 2018 has increased by 11.8%. This study aims to determine factor that related to iron and folic acid supplement consumption. Methodology: Research articles are reviewed from several sources, which is Pubmed, Science Direct, and Google Scholar. The article written by English with key words for compliance with iron tablets and folic acid, side effects and other influencing factors. This article search starts from 2009 to 2019 and related books. Results: Anemia in adolescents is still a problem. Factors that influence the regularity of drinking iron and folic acid supplementation include the side effects caused, how to consume the iron and folic acid supplement correctly without combine with other drinks, socio-cultural factors, and difficulties swallowing tablets. Conclusion: Policies that need to be implemented are health promotion by increasing knowledge about anemia, the importance of iron and folic acid and conducting periodic supervision. This supervision can be done by carrying out the movement of taking iron tablets and folic acid simultaneously at the same time and day that is directly supervised by the school teacher.